Two routes to land: Genomic underpinnings of parallel aerial egg deposition in aquatic Old-World Pila and New-World Pomacea (Ampullariidae) - YL Zhou; Huawei Mu; Xueying Nie; Yue Gao; Hui Wang; Ling Fang; Tiangang Luan; Monthon Ganmanee; Jian‐Wen Qiu; Jin Sun; Jack Chi‐Ho Ip (bioRxiv (Cold Spring Harbor Laboratory), 2025)
Abstract The parallel evolution of aerial oviposition in Old-World Pila and New-World Pomacea apple snails—diverged since the Gondwanan breakup yet convergently transitioning from aquatic to terrestrial egg deposition—offers a powerful model for probing genomic adaptations underpinning key evolutionary innovations. We generated chromosomal-level genomes of Pila celebensis and Pila pesmei , revealing a genus-specific doubling in genome size driven by transposable element expansions. Parallel chromosomal rearrangements linked to environmental sensing, stress responses, and metabolism were identified in both lineages. Gene family analyses uncovered parallel expansions in cellulases, immune genes, and environmental sensors, alongside convergent positive selection in aquaporins critical for aerial osmoregulation. Strikingly, proteomics of egg perivitelline fluid (PVF) highlighted parallel adaptations in the PV1 protein family, where increased hydrophobicity enhances desiccation resistance in aerially deposited eggs. Phylogenetic and structural evidence traced PV1’s likely origin to horizontal gene transfer (HGT) from a virus in the Ampullariidae ancestor, with subsequent duplications enabling lineage-specific aerial adaptations. Despite distinct genomic trajectories, Pila and Pomacea demonstrate that parallel molecular evolution and HGT-driven innovation facilitated their convergent transition to terrestrial reproduction, providing unprecedented insights into the genomic architecture of adaptive convergence.
Keywords: Mollusks and Parasites Studies; Invertebrate Taxonomy and Ecology; Protist diversity and phylogeny